2019
DOI: 10.1111/bjdp.12297
|View full text |Cite
|
Sign up to set email alerts
|

Children's selective trust: When a group majority is confronted with past accuracy

Abstract: In two experiments, 3-to 5-year-old children were tested for their preferences when seeking and accepting information about novel animals. In Experiment 1, children watched as two adults named unfamiliar animalsone adult was predominantly accurate, whereas the other was predominantly inaccurate, as judged by a teacher. In a subsequent test phase, participants viewed additional unfamiliar animals and were invited to endorse one of two conflicting names. Either the predominantly accurate or the predominantly ina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
0
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 32 publications
0
0
0
Order By: Relevance
“…It was found that they normally consider past accuracy more important than other epistemic cues. For example, 3- to 6- year-olds were more likely to endorse claims from someone who has proven accurate in the past, even if the claims conflicted with those of the majority (Einav, 2014 ; Sampaio et al , 2019 ; Scofield et al ., 2013 ). However, children do not always treat a previously inaccurate informant as unreliable.…”
Section: Resultsmentioning
confidence: 99%
“…It was found that they normally consider past accuracy more important than other epistemic cues. For example, 3- to 6- year-olds were more likely to endorse claims from someone who has proven accurate in the past, even if the claims conflicted with those of the majority (Einav, 2014 ; Sampaio et al , 2019 ; Scofield et al ., 2013 ). However, children do not always treat a previously inaccurate informant as unreliable.…”
Section: Resultsmentioning
confidence: 99%
“…Others have found evidence showing that children under age six are swayed by the presence of a majority, even when there are other cues to information quality available: for example, 4-year-olds did not consistently endorse an informant with a past history of success over a conflicting majority with unknown expertise (Burdett et al, 2016;Sampaio et al, 2019).…”
Section: Preferences?mentioning
confidence: 99%
“…When the reliability of consensus is weakened by other cognitive factors, they will choose dissenter. Sampaio et al (2019) found two people with different accuracy in the familiarization phase (80%vs.20%), compared with the consensus respectively, facing a dissenter with 20% accuracy, 3-5-year-olds trusted a group; facing a dissenter with 80% accuracy, Children trusted a dissenter ;Zhang Jing et al (2020) found that inaccurate group (accuracy 0%) and accurate dissenter (accuracy 100%) , Four-year-old children make trust judgments based on consensus, Children aged 5-6 years old make trust judgment according to the accuracy; Bernard et al (2015) found that only 6 years old children prefer to trust an accurate (100% accurate) dissenter, Children aged 4 and 5 trust inaccurate majority (0% accuracy). In the conflict of consensus and accuracy, which age is the turning point of young children towards accuracy characteristics?…”
Section: Introductionmentioning
confidence: 99%
“…The accuracy of the classical object naming paradigm considers the rationality of the familiarization phase trials in the selective trust research paradigm (Koenig et al, 2004;Bernard et al, 2015;Sampaio et al, 2019). Corriveau ( 2013) has used four trials to control 100% vs.0% and 75% vs.25% accuracy, Sampaio et al (2019) used 5 trials to manipulate 80% vs. And 20% of the accuracy.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation